Lao PDR - Civil Service Pay and Compensation Review : Attracting and Motivating Civil Servants - World Bank (World Bank, 2012)
Lao PDR is at a point on its development trajectory where strategic attention to administrative performance is crucial. An efficient and high-performing civil service, with the compensation and human resource management systems to attract and motivate qualified personnel, will be essential to Lao PDR's development efforts. The ministerial-level Public Administration and Civil Service Authority (PACSA) is currently spearheading the drafting of a comprehensive new civil service management strategy that will be implemented over the period 2010-2020, with a number of important reforms to strengthen the civil service anticipated to take place within the next five years. Key objectives include improvements in human resource policies and planning, salary reform, and enhanced performance management. In order to present as comprehensive a picture as possible of the Lao civil service pay and compensation system, and its strengths and challenges, this report comprises four chapters. The first characterizes the Lao civil service in perspective. The second examines how civil servants are compensated. The third assesses whether they are compensated adequately. The fourth summarizes civil servants own characterization of their incentives in both compensation- and non-compensation-related terms. A brief conclusion points to a set of principles for civil service reform and outlines three sequenced steps toward achieving a more rational civil service pay and grading system.